Upaya Untuk Meningkatkan Prestasi Belajar PAI Dengan Menggunakan Model Pembelajaran Index Card Match (ICM) di Kelas IV SDN 25 Tanjung Beringin - Amelia Putri, Santi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in the subject of Faith in the Messengers of Allah Swt. through the use of the Index Card Match (ICM) method at SDN 25 Tanjung Beringin. The research was conducted in two cycles, with the first cycle showing 58% of students achieving learning mastery, and the second cycle reaching 100% mastery. In the second cycle, the use of educational videos and group discussions with the ICM method proved to be effective in enhancing student understanding. The results of this study indicate that the ICM method can improve student activity, engagement in learning, and overall learning outcomes